The Use of Agricultural and Logging Waste as Litter Materials in Broiler Rearing - Mugiyono, Sigit; Sukardi, Sukardi (ANIMAL PRODUCTION, 2003)
A research has been conducted to study the use of agricultural and logging waste as litter materials in broiler rearing. Experimental method was used with completely randomized design. The treatments were the use of agricultural and logging waste as litter materials (L) consisting of L1 = rice hulls, L2 = rice straw, L3 = wood draff and L4 = saw dust. Parameters observed were litter moisture, production index and income over feed and litter cost (IOFLC). The experiment used 96 chickens, which were divided, into 24 cages. Statistical analysis showed that the use of agricultural and logging waste significantly (P<0,01) affected the litter moisture, production index and IOFLC. It could be concluded that rice straw, small plane wood and saw dust could be used as litter materials in broiler rearing. (Animal Production 5(1): 42-49 (2003)Â Key words: Agricultural, Logging, Waste, Litter, Broiler